A Method for Setting Northern Bobwhite Population and Habitat Objectives for Large Landscape Partnerships - James Giocomo; William Vermillion; Stephen DeMaso; Barry Wilson; Jon Hayes; Kenneth Gee; Jesús Franco; Aimee Roberson; Robert Perez; Jeff Raasch; Bill Bartush; Benjamin Kahler (National Quail Symposium Proceedings, 2017)
Population and habitat objectives are the foundation for many conservation actions. Often objectives set at one scale are difficult to translate to larger or smaller scales. Three bird habitat Joint Ventures, Gulf Coast, Oaks & Prairies, and Rio Grande, working cooperatively with the Gulf Coast Prairie Landscape Conservation Cooperative, have a common objective to stabilize northern bobwhite (Colinus virginianus) populations in four Bird Conservation Regions. We cooperatively developed a method using the North American Breeding Bird Survey trend for several scenarios with different time horizons (10-, 20-, 30-year, or longer), the spring home range size, and the per acre cost of habitat management actions, to set spring population and habitat objectives and projected costs. The spring population objectives can easily be converted to fall population objectives using the percent summer gain. We provide an example of how three Joint Ventures could use this methodology to set bobwhite objectives within their geographies and then scale those objectives up to the next larger geography, a Landscape Conservation Cooperative geography. This methodology can be used by other multi-state partnerships (e.g., Joint Ventures and Landscape Conservation Cooperatives) across the bobwhite range to provide the bobwhite conservation community meaningful objectives at regional and national scales.
Keywords: Colinus virginianus; northern bobwhite; habitat objective; joint venture; landscape conservation cooperative; partnership; population objective